2020
DOI: 10.22271/fish.2020.v8.i5b.2313
|View full text |Cite
|
Sign up to set email alerts
|

The current status of inland fisheries in Basrah province, Iraq

Abstract: The current status of species composition, total catch, fishing effort and their landing trends in six fish landing locations in the inland waters of Basrah province, Iraq from 2017 to 2019 were assessed. A total of 15 species in 5 families were recognized in the inland fisheries. The maximum total catch was 2061.5 t in 2019, whereas 1740.7 t in 2017 and 1804.2 t in 2018. The total catches show a clear increasing trend from 2017 to 2019. Cyprinus carpio dominated the overall catch (29.2%), followed by Planiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The overall values of the biomass diversity index of each species were 2.07 in 2020 and 2.12 in 2021. Abood and Mohamed (2020) found that the overall values of biomass diversity of each species ranged from 2.10 in 2017 to 2.11 in 2019. The total landings of various fish species and their contributions to the inland fisheries during 2020 and 2021 are presented in Table 3.…”
Section: Catch Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall values of the biomass diversity index of each species were 2.07 in 2020 and 2.12 in 2021. Abood and Mohamed (2020) found that the overall values of biomass diversity of each species ranged from 2.10 in 2017 to 2.11 in 2019. The total landings of various fish species and their contributions to the inland fisheries during 2020 and 2021 are presented in Table 3.…”
Section: Catch Compositionmentioning
confidence: 99%
“…Nasir and Khalid (2017) 2015). C. carpio and tilapia species catch showed steady increasing trends in the last years in Basrah province (Nasir and Khalid, 2017;Abood and Mohamed, 2020). During the last few years, the Basrah Agriculture Directorate has released large numbers of young carp from its hatcheries (Personal communication).…”
Section: Catch Compositionmentioning
confidence: 99%
“…Later, Ref. [13] investigated the species composition, total catch, fishing effort and landing trends in the inland waters of Basrah province during 2017-2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[31] recorded its presence in the Shatt Al-Arab River, while tilapia species invaded Iraqi waters and first recorded in the Euphrates River near Musaib City, the middle of Iraq during 2007 [32] after that they recorded in Basrah waters during 2009 and 2015 [33]. C. carpio and tilapia species catch showed steady increasing trends in the last years in Basrah province [12,13]. During the last few years, the Basrah Agriculture Directorate has released large numbers of young carp from its hatcheries (Personal communication).…”
Section: Monthly and Annual Catchesmentioning
confidence: 99%
“…Now, the tilapia species were found in different waters of the country [3][4][5][6][7][8][9][10][11][12]. The total landing of tilapia species by the inland artisanal fisheries of Basrah Governorate was 864,700 kg during 2017-2019 and came in the third rank with 15.4% of the total fish landings during this period [13].…”
Section: Introductionmentioning
confidence: 99%